ANALISIS KADAR KAFEIN PADA BIJI KAKAO (THEOBROMA CACAO L.) ASAL KABUPATEN MAMUJU UTARA SULAWESI BARAT DENGAN METODE SPEKTROFOTOMETRI UV-VIS - Razak, Rais; Mappacanda, Aco (Jurnal Ilmiah As-Syifaa, 2011)
Research was conducted to determine the caffeine content in cocoa beans from West Sulawesi North Mamuju with UV-VIS spectrophotometric method at a wavelength of 272 nm. This study used two examples of types of Criollo cocoa and Forastero taken from North Mamuju. Qualitative analysis using mureksid reaction that produces the color purple and brown precipitate region contribute iodide reaction in which in accordance with the reaction on caffeine standard. Analysis of caffeine content was conducted using ultraviolet spectrophotometry at a wavelength of 272 nm and obtained levels - average caffeine for example A  : 4,329mg/0,05g and B: 4,186mg/0,05g.Key words : .Analysis, caffeine, Theobroma cacao L, UV-VIS spectrophotometric.